On the history of ephemeral conditional subordinators: Evidence from the Penn Parsed Corpora of Historical English - Blanco-García, Cristina (Complutense Journal of English Studies, 2024)
This article discusses the history of a selection of ephemeral adverbial subordinators (Kortmann 1997, 301), i.e., those that mainly originated in the Early Modern English period (16th -17th centuries) but whose subordinating function, however, either became obsolete rather quickly or was subject to further restrictions beyond this period. This phenomenon was particularly frequent in the CCC relations, these are: causality, conditionality and concessivity. The present article analyses a selected number ephemeral conditional subordinators and compares them with the prototypical conditional subordinator if. The methodology is corpus-based, and I examine the data in the Penn Parsed Corpora of Historical English. The examples discussed reveal that ephemeral conditional subordinators are scarce and serve as a clear illustration of the concept of ephemerality in the realm of adverbial subordinators.